2016
DOI: 10.1039/c5ra23250c
|View full text |Cite
|
Sign up to set email alerts
|

Energetic hybrid polymer network (EHPN) through facile sequential polyurethane curation based on the reactivity differences between glycidyl azide polymer and hydroxyl terminated polybutadiene

Abstract: To improve the thermo-mechanical properties of glycidyl azide polymer and hydroxyl terminated polybutadiene based propellants, a facile sequential polymerization approach was used to prepare an energetic hybrid polymer network by stepwise curation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
(52 reference statements)
0
14
0
Order By: Relevance
“…GAPs with various topological structures have been designed and prepared (branched GAPs, star‐type GAP oligomers, diblock or triblock copolymers of GAPs, grafting compounds of GAPs, etc.) in order to overcome some problems of general linear GAPs in application, such as low molecular weight (2000–5000 g mol −1 ), short polyether main chain, poor low‐temperature properties and so on . In some respects, many of these different GAP‐based polymers exhibit better performances than linear GAPs.…”
Section: Introductionmentioning
confidence: 99%
“…GAPs with various topological structures have been designed and prepared (branched GAPs, star‐type GAP oligomers, diblock or triblock copolymers of GAPs, grafting compounds of GAPs, etc.) in order to overcome some problems of general linear GAPs in application, such as low molecular weight (2000–5000 g mol −1 ), short polyether main chain, poor low‐temperature properties and so on . In some respects, many of these different GAP‐based polymers exhibit better performances than linear GAPs.…”
Section: Introductionmentioning
confidence: 99%
“…19 The appearance of strong peaks at 1225 and 1161 cm À1 was attributed to -CF 3 , [20][21][22] the appearance of peaks at 1412-1534 cm À1 was attributed to the characteristic absorption of TDI, and the characteristic absorption peaks at 3311, 1710 and 1533 cm À1 certied the formation of urethane linkage. 23,24 Therefore, these results gave strong evidence that the prepolymer process indeed occurred by the formation of PBFMO-b-PNMMO. NMR analysis was used to determine the real composition of the as-synthesized PBFMO-b-PNMMO, which is shown in Fig.…”
Section: Synthesis Of Pbfmo-b-pnmmo-based Thermoplastic Elastomersmentioning
confidence: 60%
“…Semsarzadeh and Navarchian reported that during thermal decomposition of EPU, the diisocyanates may be dimerized to form carbodiimides, which can further react with the urethane groups to form a crosslinked structure, which needs more energy to break. The formation of a highly crosslinked network structure in EPU4 is determinant for the observed enhancement in the thermal stability …”
Section: Resultsmentioning
confidence: 99%